Assessment of knowledge, attitudes, and practices regarding prevention of tuberculosis among clients visiting Upazila Health Complex outpatient department in Bangladesh: an interview-based study - Lutfun Nahar; Abu Bakkar Siddique; Nishat Tamanna Omi; Hasib Ahmed Bhuiyan; Mithila; Sher Mostafa Sadiq Khan (Discover Public Health)
Abstract Background Tuberculosis remains a significant public health concern globally, particularly in low- and middle-income countries like Bangladesh. This study aimed to assess the knowledge, attitudes, and practices related to TB prevention among clients at the Upazila Health Complex in Bangladesh to understand TB prevention related knowledge and preventive behaviors. Methods This cross-sectional, interview-based study was conducted from November 1 to December 31, 2023, among clients visiting the outpatient departments of Upazila Health Complexes in Munshiganj District, Bangladesh. A sample of 453 participants was selected through convenience sampling, and data on socio-demographics and KAP regarding TB prevention were collected using structured questionnaires. Data analysis was performed using Microsoft Excel 2021, SPSS version 26.0 (Chicago, IL, USA), and STATA version 15.0. Results The study found moderate TB knowledge (mean score = 8.68), favorable attitudes (mean score = 24.02), and strong preventive practices (mean score = 23.99) among participants. Younger age, higher education, and internet access positively influenced TB knowledge, while unemployment and semi-urban residence had negative associations. Positive attitudes were linked to higher education, rural residence, and internet access, and preventive practices were improved by higher education, underlying health conditions, and healthcare accessibility. Conclusion The study highlights the importance of targeted public health interventions focusing on education, healthcare accessibility, and awareness to strengthen TB prevention. Key determinants such as age, education level, employment status, residence type, and access to healthcare significantly impact TB knowledge, attitudes, and practices. To improve TB-related outcomes, initiatives should prioritize education and resources in semi-urban areas and support vulnerable groups through community engagement and tailored health programs.